Algoritmo Geral para a Procura De Códigos Treliça Ótimos Baseados em Partições de Reticulados - Rosa, E. M.; Borelli, W. C.; Farrel, P. G. (Journal of Communication and Information Systems, 2017)
In this paper a general algorithm for the search of optimum q-ary trellis codes, based on lattices and cosets, is proposed. The algorithm incorporates the procedures introduced for binary codes in [2],[4] and generalizes the search for alphabets that are rings with q elements, Z_q. New characteristics were incorporated to the algorithm, providing a faster and more efficient search for the optimum codes than in [3],[4],[5]. Numerical examples are presented in details for binary scheme with the Z^2/ hetaZ^2 partition and for a ternary scheme with the A_2/9A_2 partition.